Windows Server 2003 Pocket Administrator - Ruest, Nelson (McGraw-Hill, 2011)
This handy resource offers busy network administrators clear and concise information for daily on-the-job tasks--all in a portable format. Key management tasks are presented in logically organized sections. You’ll get details on file, print, application, mail, terminal, streaming media, and remote servers--and much more.